Therapeutic Impact of Deepana-Pachana(appetizer-digestives) In Panchakarma: An Overview - choudhary, Kshiteeja; gupta, Nidhi; mangal, Gopesh (International Research Journal of Ayurveda & Yoga, 2021)
Introduction: Deepana and Pachana (appetizer-digestives) have equal significance in both Shodhana (bio Purification) and Shamana treatment (Pacification Treatment) modalities of Ayurveda. Deepana and Pachana Karma play an important role as Purvakarma of Shodhana (bio-purification) procedures. Purvakarma (pre operative procedure) refers to the preparation of body for the Panchakarma therapies and it is crucial for the body to achieve the complete benefits of therapies. Objective: To understand the importance of proper Deepana and Pachana therapy(appetizer-digestives) in Panchakarma. Review Method: For this review article, various Ayurvedic texts- Charaka Samhita, Sushruta Samhita and Astang Haridayam with Chakrapani and Arundatta Teeka are studied. Peer-reviewed clinical studies, review articles, various websites etc. are considered. Discussion and conclusion: Deepana Pachana (appetizer-digestives) can complete in one day or over many days, till Nirama Awastha (without ama condition) occurs. So the drugs for Deepana and Pachana (appetizer digestives) are varying person to person according to Parkrti(nature), Kostha (bowel) , Dosha, Bala(Strength) etc.